Elephant Population Status, Distribution and Conservation Threats in Kibale National Park, Uganda. - Aleper, Daniel; Andama, Edward; Adriko, Kennedy (East African Journal of Environment and Natural Resources, 2021)
This study focused on the estimation of the African elephant population, distribution, and conservation threats in Kibale National Park (KNP) from August 2019 to February 2020. The objectives of the study were to: generate population estimates, distribution and assess threats to the conservation of elephants. The line transect method based on the dung pile count density from line transect, dung decay, and defecation rates were used to estimate the elephant population. The density was calculated by multiplying the decay rate with the ratio of dung density to defecation rates. The overall elephant population was estimated at 566.27 (95% Confidence limits 377.24-850.02). This was a slow increase from 393 recorded in 2005 to 566 animals in 2019. Elephants were widely distributed within the park and these pose challenges such as increasing human-elephant conflicts. With a steady increase in the elephant population and seasonal movements out of the park, there is a need to continuously monitor elephant population growth and ranging behaviour vis-a-vis available habitat range and how this impacts ecosystem dynamics and human-elephant conflicts